Expression of tau mRNA and soluble tau isoforms in affected and non-affected brain areas in Alzheimer's disease - Boutajangout, A.; Boom, A.; Leroy, K.; Brion, J.P. (FEBS letters, 2004)
In Alzheimer's disease (AD), selective expression of tau isoforms might underlie the susceptibility of different brain areas to develop neurofibrillary tangles and this pattern might change in the disease. In this study, we have analyzed in control subjects and in sporadic AD patients the pattern of expression of tau mRNA and tau proteins in areas unaffected (cerebellar cortex, white matter), moderately affected (occipital striate cortex, thalamus, caudate nucleus, and putamen) or strongly affected by neurofibrillary tangles (temporal and frontal associative cortex). After RT-PCR amplification, five products corresponding to the tau mRNAs containing exons 2 and 3, exon 2, without exons 2 or 3, with exon 10 and without exon 10 were identified. In control subjects, these five PCR products were present in all areas except in white matter, where transcripts with exons 2 or exons 2 and 3 were not identified. In AD patients, the same pattern of transcripts was observed in different areas, regardless of the presence of neurofibrillary lesions. After dephosphorylation of soluble tau proteins, the six tau isoforms were identified in the same areas by immunoblotting, including in the white matter, suggesting that most tau isoforms with exons 2 and 3 are transported along axons. The relative expression of 0N3R isoforms was higher in the temporal cortex than in the cerebellar cortex, both in control and AD subjects. The qualitative pattern of expression was identical in subjects with or without an APOE4 allele. Our results suggest that splicing regulation of the tau gene and the relative expression of tau isoforms are not significantly changed in sporadic cases of the disease, although differential expression of tau isoforms in temporal cortex might underlie this brain area susceptibility to neurofibrillary tangles formation.